Strategies To Enhance Transdermal Drug delivery - Mais Saadallah; Omar Hamid (University of Mosul, 2021)
Background: Transdermal drug delivery system (TDDS) is a promising delivery system that provides controlled drug release at a predetermined time. It has many advantages such as bypassing first-pass effect, increase patient convenience by providing single application rather than multiple dosing frequencies, and extends the action of short half-life drugs. There are three ways for drug penetration into the skin either via appendageal (shunt routes), intracellular route, and intercellular route. Permeation of drug substances through the stratum corneum remains a great challenge because it is the rate-limiting step for permeation for most molecules. Aim: This review article highlights the advances and limitations of the strategies to enhance transdermal delivery of the drugs into the skin, including both physical and chemical methods. Conclusion: The transdermal drug delivery system represents a good alternative for oral and parenteral therapy. Various penetration enhancing strategies have been successfully employed to enhance the permeation of low molecular weight molecules. For high molecular weight molecules, physical strategies such as microneedles can be used.